2002
DOI: 10.1046/j.1462-5822.2002.00165.x
|View full text |Cite
|
Sign up to set email alerts
|

Delinking of S phase and cytokinesis in the protozoan parasite Entamoeba histolytica

Abstract: SummaryThe alternation of DNA replication in S phase and chromosome segregation in M phase is a hallmark in the cell cycle of most well-studied eukaryotes and ensures that the progeny do not have more than the normal complement of genes and chromosomes. An exception to this rule has been described in cancer cells that occasionally become polyploid as a result of failure to restrain S phase despite the failure to undergo complete mitosis. Here, we describe the cell division cycle of the human pathogen, Entamoeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 18 publications
(38 reference statements)
2
47
0
Order By: Relevance
“…Our previous studies have shown that an increased population of cells with 4ϫ or more genome contents identified by flow cytometry could be due to an increase in the number of multinucleated cells or in the number of genome copies in uninucleated cells (12,13,18). An increase in the number of multinucleated cells signifies a delay in cytokinesis, while an increase in the DNA content of individual nuclei suggests Increased expression of Ehformin-1 and -2 delays both cell division and mitosis.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Our previous studies have shown that an increased population of cells with 4ϫ or more genome contents identified by flow cytometry could be due to an increase in the number of multinucleated cells or in the number of genome copies in uninucleated cells (12,13,18). An increase in the number of multinucleated cells signifies a delay in cytokinesis, while an increase in the DNA content of individual nuclei suggests Increased expression of Ehformin-1 and -2 delays both cell division and mitosis.…”
Section: Resultsmentioning
confidence: 98%
“…Log-phase cultures may accumulate multinucleated cells containing heterogeneous amounts of DNA (12,18). Our previous observations suggest that genome reduplication without mitosis and irregularity in cytokinesis contribute maximally to the observed heterogeneity (12,36).…”
mentioning
confidence: 87%
“…EhDead1 mRNA is over expressed in S phase of cell cycle EhDEAD1 exhibits 70% homology to yeast DED1 RNA helicase (Table 1), which participates in cell cycle regulation (Warbrick and Glover, 1994;Forbes et al, 1998;Grallert et al, 2000). Although axenic cultures of E. histolytica are made of a heterogeneous population of cells with varying DNA content, various studies have described cell cycle phases in log phase cultures in distinct strains or clones (Orozco et al, 1988;Dvorak et al, 1995;Gangopadhyay et al, 1997;Vohra et al, 1998;Das and Lohia 2002;Dastidar et al, 2007). Here, we used trophozoites of clone L6, which is routinely synchronized by the mitotic blocker colchicine in our laboratory and whose cell cycle phases lasting is well characterized (Orozco et al, 1988;Marchat et al, 2003).…”
Section: Rehdead1 48 Has Atp-dependent Rna Unwinding Activity In Vitromentioning
confidence: 99%
“…Similar distribution was observed in bi-and tri-nucleated cells (quantitative data not available). Genome content of individual nuclei was estimated by DAPI fluorescence in a scanning cytometer and data from 2000 nuclei was normalized (Adapted from Das and Lohia 2002). Average distribution (%) of genome content in uni-nucleated cells was calculated from more than three independent sets of experiments.…”
Section: Genome Reduplication Occurs Commonly In Entamoeba Trophozoitesmentioning
confidence: 99%
“…3 Heterogeneity of genome content in E. histolytica trophozoites during vegetative growth. This cartoon is summarized from observations presented in Gangopadhyay et al (1997a), Das and Lohia (2002) and Dastidar et al (2007). Majority of cells in log phase of growth are euploid with single nucleus containing 1x-2x genome contents (A).…”
Section: Irregular Dna Synthesis and Chromosome Segregation: Observatmentioning
confidence: 99%